AUTOMATED PLANNING OF FLIGHT TRAJECTORY UNDER CROP DUSTING - Dmitry Y. Parshin; Kopkin Andrey S. (Advanced Engineering Research)
Microlight trajectory scheduling and prediction methods for crop dusting are given. The techniques o f the correction and transformation of coordinates from the satellite navigation syste m, and of the advanced smoothing for exclu ding the inertia affection of the ‘pilot — microlight’ system, are offered.